(untitled) (International Journal of Engineering and Computer Science, 2017)
Rich Internet Applications provides rich user experience owing to its advanced user interfaces and highly responsive design implementation. JavaScript, Ajax, Flash etc. are some of the widely used technologies to build such immense Rich internet applications. They offer great functionality to the applications in less lines of code. But on the flipside, it has the limitation, that Search Engines find it hard to index the contents of RIA.Temporary solutions does exists, but they are effective only up to some extent. This paper discuses some of the challenges faced by RIA developers to make their application Search engine friendly and some commonly followed workarounds to override these limitations. It also deeply examines these solutions and identify flaws or limitations of these methods, if any